RESPONSE SURFACE METHODOLOGY VIA DESIRABILITY FUNCTION TECHNIQUES FOR OPTIMIZING CORRELATED RESPONSES OF ELECTRICAL CONDUCTIVITY AND TOTAL DISSOLVED SOLIDS OF SELECTED BOREHOLE WATER (FUDMA JOURNAL OF SCIENCES, 2020)
The health benefits in the description and observation of quantitative contents of quality parameters present or contained in any water source cannot be underestimated as they determine selection of best choice from available water sources for different intended uses as well as resource consumption. It also helps to compare the observed quantity of the quality with the acceptable standards or limits to get desired results. Physical parameters like pH, temperature, electrical conductivity (EC) and total dissolved solids (TDS) among others are determined by present of other chemical properties like Cations (Mg2+, Ca2+, Na+, etc), Anions (Cl-, NO3-, SO42+, etc), heavy metals and other dissolved materials during the course of its formation in different proportions and amounts. This study observed EC and TDS of 20 selected boreholes as two close and correlated water quality parameters as well as two of the major water quality parameters that account for overall quality of any water source, despite their different quantitative contents and physical features, they are likely determined by the same set of cations and anions with similar constraint equations. In contrast to linear programming, multiple criteria optimization models were fitted for EC and TDS using Response Surface Methodology via desirability techniques, optimal values obtained in this case measured against several criteria are found to lie between acceptable standards limits for drinking water, other numerical values and descriptive features in the final results reflect that the response equations obtained were well fitted.
Keywords: Desirability Function, Electrical Conductivity, Optimal value, Response Surface Methodology, Total Dissolved Solids, Water Quality Parameters